Disability and labour force participation in Cameroon - (:unkn) unknown (My University, 2016)
Inclusive Growth in Africa analyzes the concept of inclusion within the challenges facing Africa’s rapidly growing economies, where rising affluence for some has been accompanied almost everywhere with rising inequality. Using a combination of political economy analyses, sector studies and econometric models, the contributors delve into a range of areas associated to the new realities on the continent. Topics covered include issues of disability, corruption, capital flight, and their implications for economic sustainability. There is also a discussion of the impact on development of dependence on externally determined prices for Africa’s natural resources. Other sector analyses look at agriculture and wind power, and the innovations required to make a difference for the poorer majority. The book comprises of a rich array of essays on socio-economic inclusion in Africa by authors drawn from academia, African think tanks and international organizations. It would be of interest to scholars and students of many disciplines, including: Economics, Sociology, Development Studies, and African Studies.
Keywords: African Research